2018
DOI: 10.1587/transcom.2017nri0002
|View full text |Cite
|
Sign up to set email alerts
|

Resource Management Architecture of Metro Aggregation Network for IoT Traffic

Abstract: SUMMARY IoT (Internet of Things) services are emerging and the bandwidth requirements for rich media communication services are increasing exponentially. We propose a virtual edge architecture comprising computation resource management layers and path bandwidth management layers for easy addition and reallocation of new service node functions. These functions are performed by the Virtualized Network Function (VNF), which accommodates terminals covering a corresponding access node to realize fast VNF migration.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…For cost‐efficient end‐to‐end cloud networking, minimum‐cost mapping must be found that efficiently aggregates traffic from numerous AGNs to datacenters, while reducing the consumption of physical link resources. In addition, metro/access networks account for most of the network cost . Thus, virtual network embedding problems in metro aggregation networks must be solved for cost‐efficient cloud networking.…”
Section: Introductionmentioning
confidence: 99%
“…For cost‐efficient end‐to‐end cloud networking, minimum‐cost mapping must be found that efficiently aggregates traffic from numerous AGNs to datacenters, while reducing the consumption of physical link resources. In addition, metro/access networks account for most of the network cost . Thus, virtual network embedding problems in metro aggregation networks must be solved for cost‐efficient cloud networking.…”
Section: Introductionmentioning
confidence: 99%